Kindergarten in Krusevac from 1929 till 1935 - Lazarević, Vladan R. (Sinteze - časopis za pedagoške nauke , književnost i kulturu, 2022)
The work of the Kruševac kindergarten in the period 1929-1935 is described based on statistical information which was sent to  Ministry of education of Kingdom of Yugoslavia. It describes how the kindergarten was financed, how much it received funds from the local self-government and Kingdom itself. The structure of children by age, nationality and religion in that period is given. It also reports on children's illnesses, absences, the number of enrolled children in one school year. Data are also given about the entertainer (educator) who was in the kindergarten, her affiliation with various other organizations such as Red Cross. The structure of parents and their occupations are also given. For the school year 1931/32.  there are no data.
Keywords: children; kindergarten; Kruševac; Archival Records; Ministry of education; statistical data